The Neutrophil-to-lymphocyte Ratio as a Prognostic Factor for Patients with Urothelial Carcinoma of the Bladder Following Radical Cystectomy: Validation and Meta-analysis - Lucca, Ilaria; Jichlinski, Patrice; Shariat, Shahrokh F; Rouprêt, Morgan; Rieken, Malte; Kluth, Luis A; Rink, Michael; Mathieu, Romain; Mbeutcha, Aurelie; Maj-Hes, Agnes; Fajkovic, Harun; Briganti, Alberto; et al. (European urology focus, 2016)
BACKGROUND: The neutrophil-to-lymphocyte ratio (NLR) as a marker of systemic inflammatory response has been proposed as a prognostic factor for patients with urothelial carcinoma of the bladder (UCB) following radical cystectomy (RC). OBJECTIVE: To validate NLR as a prognostic biomarker and to perform a pooled meta-analysis. DESIGN, SETTING, AND PARTICIPANTS: The NLR was assessed in 4061 patients within 30 days before RC. A systematic review of the literature was undertaken using electronic databases. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Associations with overall survival (OS) and cancer-specific survival (CSS) were evaluated using Cox models. Hazard ratios (HRs) were pooled in a meta-analysis using random-effects modeling. RESULTS AND LIMITATIONS: A high NLR (≥2.7) was associated with advanced pathological tumor stages (p<0.001), lymph node involvement (p<0.001), lymphovascular invasion (p=0.008), and positive soft0tissue surgical margins (p=0.001). In multivariate analyses, a high NLR was independently associated with both OS (HR 1.11, 95% confidence interval [CI] 1.01-1.22; p=0.029) and cancer-specific survival (CSS) (HR 1.21, 95% CI 1.07-1.37, p=0.003). The discrimination of the multivariate models increased by 0.2% on inclusion of NLR. Five studies were included in the meta-analysis. The HR for NLR greater than the cutoff was 1.46 (95% CI 1.01-1.92) for OS and 1.51 (95% CI 1.17-1.85) for CSS. Limitations include the retrospective study design and the lack of standardized follow-up. CONCLUSION: In patients with UCB treated with RC, a high preoperative NLR is associated with more advanced tumor stage, lymph node metastasis, and worse prognosis. The NLR may be a readily available and useful biomarker for preoperative prognostic stratification. PATIENT SUMMARY: We investigated the neutrophil-to-lymphocyte ratio (NLR) as a prognostic marker in patients with bladder cancer treated with radical cystectomy. We found that a high NLR is associated with worse oncologic outcomes, suggesting it could play a role in risk stratification.
Keywords: Survival; Urothelial carcinoma of the bladder; Meta-analysis; Radical cystectomy; Neutrophil-to-lymphocyte ratio